Spatiotemporally co-delivery of triple therapeutic drugs via HA-coating nanosystems for enhanced immunotherapy - Chaoqun Ma; Yichao Duan; Chaohui Wu; Erjuan Meng; Pingping Li; Zhenzhong Zhang; Chunhua Zang; Xueling Ren (Elsevier, 2021)
There is growing empirical evidence that certain types of chemotherapy and phototherapy trigger immunogenic cell death and enhance the therapeutic anticancer efficacy of genetic immunotherapy. However, the main challenge is spatiotemporally co-delivering different drugs to maximize the therapeutic index of the combination therapy. In this study, a drug delivery system (HTCP-Au/shPD-L1/DOX) was designed with a polysaccharide-wrapped shell and a condensed DNA core. To construct the HTCP-Au vector, dodecyl side chains with a polyethylenimine (PEI) head were grafted onto hyaluronic acid, and AuNPs were grafted via Au-S bonds. During drug loading, PEI arrested shRNA plasmid DNA targeting programmed cell death ligand 1 (shPD-L1) via electrostatic interactions. It also formed a PEI-DNA core that was automatically enclosed when aliphatic hydrocarbons pulled the hyaluronic acid backbone. A hydrophobic interlayer consisting of dodecyl bridge chains between the PEI-DNA core and the hyaluronic acid shell was required to accommodate hydrophobic doxorubicin. In vitro and in vivo assays demonstrated that this core-shell drug delivery system could efficiently load and transport three different drugs and effectively target tumors. Moreover, it could activate the immune system, thereby providing promising therapeutic efficacy against tumor growth and metastasis.